Teknik Pembuatan Visual Bulu Elang Jawa dalam Karya Body Painting Fantasi Berbasis Mixed Media - Alfina Najmul Falakh; Trisnani Widowati; Novia Restu Windayani (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to explain the technique of creating visual depictions of Javan Hawk-eagle feathers in a mixed-media fantasy body painting and to evaluate the visual quality of the resulting feather textures in representing the morphological characteristics of the Javan Hawk-eagle, an Indonesian endemic animal. This study employed a descriptive qualitative method with descriptive percentage analysis. Data were obtained through an assessment process by three expert validators who evaluated the works based on indicators of elements and principles of fine art, the use of the body as a medium for aesthetic expression, creativity in beauty products, and aesthetic aspects in the beauty industry. Furthermore, percentage analysis was used to determine the visual quality of the works based on the validators' assessments. The results showed that the works obtained an average percentage of 96.7%, categorized as "very good." The feather visualization technique was carried out through the application of layering techniques, color gradation, and feather direction arrangement that follows the anatomical contours of the model's body, resulting in visual depth and a realistic impression. These results indicate that mixed-media body painting techniques can produce aesthetically pleasing and innovative feather visuals that represent the morphology of the Javan Hawk-eagle. These findings confirm that body painting can be a medium for artistic exploration of modern makeup based on local wisdom as well as a visual tool to enhance appreciation for Indonesia's endemic fauna.